EGMR 18411/11 vom 28. November 2017 , AFFAIRE MERCAN ET AUTRES c. SUISSE - Hudoc Ch (2017)
Violation de l'article 10 - Liberté d'expression-{général} (Article 10-1 - Liberté d'expression); Violation: 10;10-1